2016
DOI: 10.1007/s00428-016-1911-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ROR1 has prognostic significance in triple negative breast cancer

Abstract: Overexpression of receptor tyrosine kinase-like orphan receptor (ROR1) in a variety of human malignancies is associated with aggressive behaviour. Therapeutic agents targeting ROR1 have shown promising results in vivo and in vitro studies. In breast cancer, high-level expression of ROR1 mRNA is associated with high-grade tumours and metastasis. We investigated the prevalence and prognostic significance of ROR1 expression in triple negative breast cancer (TNBC). ROR1 was immunohistochemically stained on full-fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 24 publications
2
53
0
Order By: Relevance
“…A variety of different cancers have been found to express ROR1. 23 To date, high-level expression of ROR1 has been found to have adverse prognostic significance for patients with breast cancer, [24][25][26][27] ovarian cancer, 28,29 melanoma, 30 or Ewing sarcoma. 31 Moreover, high-level expression of ROR1 also has been associated with higher levels of AKT activation, 24,30,32,33 consistent with the notion that ROR1 signaling leading to activation of AKT may serve as a driver, not just in CLL, but also in other malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of different cancers have been found to express ROR1. 23 To date, high-level expression of ROR1 has been found to have adverse prognostic significance for patients with breast cancer, [24][25][26][27] ovarian cancer, 28,29 melanoma, 30 or Ewing sarcoma. 31 Moreover, high-level expression of ROR1 also has been associated with higher levels of AKT activation, 24,30,32,33 consistent with the notion that ROR1 signaling leading to activation of AKT may serve as a driver, not just in CLL, but also in other malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…The two ROR family members, ROR1 and ROR2, were originally found to be involved in skeletal, cardiorespiratory, and neurological development 15,16 . Rising evidence has indicated that both ROR proteins are highly expressed in multiple human cancer types, including leukemia, ovarian cancer, and breast cancer 1722 . Although ROR1 treated as a pseudokinase originally based on the observation that ROR1 was unable to be autophosphorylated 23,24 , some studies have also demonstrated the moderate autocatalytic kinase activity of ROR1 in vitro 25–27 .…”
Section: Introductionmentioning
confidence: 99%
“…It is recognized that ROR1 and ROR2 expression diminishes in adult tissue [27], with many studies indicating increased expression associated with malignant progression [3], [4], [10], [11], [12], [28], [29], [30]. We have previously found ROR2 and its receptor, WNT5A, to be upregulated in OC [13], [31], [32] patient samples and have shown in vitro that both ROR1 and ROR2 are important in OC migration and invasion, indicating a role in OC metastasis [32].…”
Section: Resultsmentioning
confidence: 99%
“…In many cases, the receptor tyrosine kinases ROR1 and ROR2 are abnormally overexpressed in tumors and associated with stem cell properties, epithelial to mesenchymal transition, and metastasis [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12]. In OC, we have previously shown that both ROR1 and ROR2 are important in cell growth, migration, and invasion [13].…”
Section: Introductionmentioning
confidence: 99%